Risk factors association of soil-transmitted Helminth infections among primary school children in Kano, northern Nigeria - Rabia, Adamu; Aziz, Nor Azwady Bin Abd; Mustafa, Muskhazli; Shohaimi, Shamarina (Hibiscus Publisher Enterprise, 2024)
Soil-transmitted helminths (STHs) are nematode species transmitted through soil contamination, primarily by eggs found in human faeces. This study investigates STH infection prevalence and associated risk factors among children attending early child centres (ECC) and primary schools in Tamburawa, Dawakin Kudu local government area, Kano State, Nigeria. A total of 560 primary school children (PSC), aged between five and sixteen, were recruited from seven selected primary schools (PS) for faecal sample collection and subsequent analysis. The formol-ether sedimentation technique used to detect the presence of STH eggs or larvae, and IBM SPSS Statistics version 26 used to analyze the results. Among the screened PSC, 357 (63.8%) were male, and 203 (36.2%) were female, while 60.4% (338 individuals) tested positive for STH infection, with 9.8% (52 individuals) exhibiting mixed infections. Notably, hookworm (35.2%), Ascaris lumbricoides (19.5%), and Trichuris trichiura (5.7%) emerged as the predominant STH species (5.7%). Gender-specific prevalence indicated a higher rate among females (32.3%) than males (28.1%). Analysis of potential risk factors revealed significant associations. Children residing in households with four or more members had a higher risk of STH infection (OR = 2.938, 95% CI: 0.195–0.578), Children who used pit latrines had a twofold increased risk of contracting STH (OR = 2.059, 95% CI: 1.682–34.712, p = 0.001). The findings of this study underscore the importance of targeted public health interventions, routine deworming initiatives, provision of potable water, and promotion of personal hygiene practices, particularly among school-aged children.